1997
DOI: 10.1007/bf01213295
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in the tumor suppressor genesp53, RB, p16/MTS1, andp15/MTS2 in human pancreatic cancer and hepatoma cell lines

Abstract: The tumor suppressor genes p53, retinoblastoma (RB), p16, and p15 encode proteins that regulate the cell cycle cooperatively by controlling the transition from G1 to S phase and may play an important role in cell growth and differentiation. To screen for abnormalities in these genes in cancer, we performed genetic analysis in six human pancreatic cancer and five hepatoma cell lines, by single-strand conformation polymorphism (SSCP) analysis, direct sequencing, and the reverse transcriptase-polymerase chain rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
27
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 18 publications
0
27
0
Order By: Relevance
“…18 Thus, it was found out that the HuH7 cell line is the one that has the greatest expression of this protein, followed by the HepG2 cells. It was confirmed the absence of p53 expression by the Hep3B2.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…18 Thus, it was found out that the HuH7 cell line is the one that has the greatest expression of this protein, followed by the HepG2 cells. It was confirmed the absence of p53 expression by the Hep3B2.…”
Section: Discussionmentioning
confidence: 99%
“…It was found that not always GLUT1 and GLUT3 are the most expressed by these cell lines. Conclusions: Our results shown that the p53 expression influences [ 18 H epatocellular Carcinoma (HCC) is one of most lethal cancers, with an increasing incidence in several regions of the world. Without specific treatment, the prognosis is very poor and survival is not prolonged.…”
mentioning
confidence: 87%
See 3 more Smart Citations